GAIA 3.0: Effects of the Coronavirus Disease 2019 (COVID-19) outbreak on sustainable development and future perspectives. (December 2020) - Berchin, Issa Ibrahim; de Andrade Guerra, José Baltazar Salgueirinho Osório
Abstract: In the past decades, the frequency of epidemics with global importance has increased significantly. Only in the first two decades of the 21st Century, the world has witnessed the epidemics of Severe Acute Respiratory Syndromes, Zika virus, Ebola virus, Yellow Fever, the new COVID-19, besides the traditional influenza and other virus and bacteria. However, due to the high level of globalization, the large-scale population flow and the high reproductive rate of the virus, COVID-19 suddenly affected several countries, infecting hundreds of thousands of people and killing dozens of thousands in the fastest unprecedented crisis ever recorded, which also led to the fasted severe economic crisis on history. This perfect storm of social, economic and health catastrophes caused by the COVID-19 pandemics, directly threatens the world's livelihood and wellbeing and jeopardize the achievement of the United Nation's Sustainable Development Goals. Sustainable development is personified by Gaia's definition, implying limits for human activities and urging for a better use of technologies and resources. Although temporary, these changes in human actions set future trends for humanity, changing many aspects of our behavior, which include impacts in culture, technology, healthcare, economy, policy, education and the environment. Which may lead to a new enlightenment based on the need for global solidarity and an urge for the implementation of sustainable development pathways, finally creating a common agenda for the future of humanity as part of the Gaia, not above it. Highlights: In the Anthropocene, humans occupy a critical role in Gaia, requiring that humanity accelerate its path towards the SDGs. Humankind is facing an unprecedented crisis, which tests the resilience of our society and boosts global solidarity. The COVID-19 pandemic urges for a common agenda for the future of humanity as part of the Gaia, not above it. International networks strengthened by the technological advances improve the sharing of knowledge and experiences. The COVID-19 pandemic made humanity critically think about its vulnerability, and the overexploitation of planetary boundaries.